Fluctuation behavior analysis of international crude oil and gasoline price based on complex network perspective. (1st August 2016) - Wang, Minggang; Chen, Ying; Tian, Lixin; Jiang, Shumin; Tian, Zihao; Du, Ruijin
Highlights: The directed and weighted networks of crude price and gasoline price were built. The evolution law of the new nodes appeared in the prices networks was obtained. The topological structure of price networks was analyzed in different periods. The dependency between the two type prices was analyzed based on network similarity. The core nodes and the distribution of the time these nodes appeared were identified. Abstract: The directed weighted networks of international crude oil and gasoline price were built in the different fluctuation periods. And then the evolution law of the new nodes in the prices networks was analyzed. The results indicated that the cumulative times of the new nodes that appeared in the crude oil and gasoline prices networks were not random but exhibited a high linear growth trend, which revealed the linear characteristics of the accumulation time of abnormal points that appeared in the process of oil price fluctuations. Based on the node strength, the calculation formula of the network similarity between the crude oil and gasoline price networks was designed, and the interdependence between the crude oil and gasoline price fluctuations was calculated, the results indicated that there was a strong interdependence between crude oil and gasoline prices in stable fluctuation periods, but the degree of dependence was significantly reduced in sharp fluctuation periods. The strength of nodes and their strength distribution, weighted clustering coefficient, and average shortest paths of the price network in different periods were calculated. The fluctuation characteristics in different periods were comparatively analyzed. The core fluctuation status and the conversion relationship between them in different periods were revealed. Finally, the important modes of price fluctuations of crude oil and gasoline were identified and the distribution characteristics of the time these modes appeared were studied.